Synergism of EGFR and c-Met pathways, cross-talk and inhibition, in non-small cell lung cancer - Puri, Neelu (Medknow Publications, 2008)
BACKGROUND: c-Met and EGFR receptors are widely expressed on cancer cells; they are implicated in the development and progression of cancer through a plethora of effects on cell cycle progression, apoptosis, motility and metastasis and are potential targets for combination therapy. EGFR receptor tyrosine kinases are currently being targeted in a number of malignancies. METHODS: Apoptosis was studied by FACS analysis using propidium iodide. EGF and HGF signaling intermediates were studied by western blotting. Cell proliferation was determined by MTT assays. Cell motility was done by time lapse confocal microscopy. RESULTS: c-Met and EGFR were both expressed in A549, H1838, H2170, SW900, SW1573, H358, SKLU-1, and H1993 non small cell lung cancer (NSCLC) cell lines. Both EGF and HGF at 100 ng/ml in medium showed a synergistic effect on cell proliferation at 48–72 h as seen by a proliferation assay in A549, H1838, and SKMES cells. In A549 and H1838 cell lines, HGF (40 ng/ml) and EGF (5 ng/ml) induced synergistic phosphorylation on c-Met (Tyr 1003/1230/1234/1235). Additionally, synergistic phosphorylation of Akt (Ser-473) and phospho-ERK1+ERK2 (Thr202/Tyr204) was also seen indicating that EGF and HGF could induce synergistic phosphorylation of important signaling intermediates. Treatment with EGF and HGF at 100 ng/ml for 2 h also leads to an additive effect in inducing cell motility (especially membrane ruffling) in H1993 cells. A novel c-Met small molecule tyrosine kinase inhibitor SU11274 and EGFR tyrosine kinase inhibitors Tyrphostin AG1478 and gefitinib (Iressa) were tested to study their effect in combination on proliferation and apoptosis in lung cancer cells. Interestingly, a synergistic effect on inhibition of cell proliferation was seen in the presence of SU11274 and Tyrphostin AG1478. 0.5 µM Tyrphostin AG1478 and 2 µM SU11274 inhibited growth by 21% and 25%, respectively; a combination of both tyrosine kinase inhibitors inhibited growth by 65%. Interestingly, EGFR inhibitor (gefitinib, Iressa) and c-Met inhibitor (SU11274) also had a synergistic effect on apoptosis in H358 cells. CONCLUSION: There was a synergistic effect of EGF and HGF on proliferation, downstream activation of signal transduction and an additive effect seen on motility. These studies show that a combination of HGF and EGF tyrosine kinase inhibitors on NSCLC, could potentially be targeted in a synergistic fashion.